Practices and infrastructures for sufficiency-oriented lifestyles - Jana Kühl (Spatial transformation: Processes, strategies, research design, 2022)
Limiting the anthropogenic environmental impact as part of the 'great transformation' is one of the central challenges of our time. However, ambitions to broaden sustainable ways of living are at odds with the consumeristic self-image of Western societies. In order to initiate a transformation, practices of sufficiency, which can already be found in nascent forms, can be used as exemplars for shaping social innovation processes. Based on alternative concepts of housing and living, resourcesaving lifestyles which diverge from established ways of living can be identified. These can lead to mental infrastructures that motivate alternative lifestyles, as well as the need for infrastructures that enable sufficiency.
urn:nbn:de:0156-08910531; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Sufficiency; sustainable lifestyles; social innovation; everyday practices; go-along